1991
DOI: 10.1002/casp.2450010203
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent self‐efficacy, self‐esteem and sexual risk‐taking

Abstract: This study investigates the sexual self-efficacy and sexual self-esteem of males and females and the relation between sexual risk-taking and these self-perceptions. Sexually active 18-yearolds were administered measures of sexual self-efficacy and sexual self-esteem and were asked about their sexual behaviour. Males had higher levels of self-esteem and were more confident than females of their ability to assert their sexual needs, but less confident that they could say no to sexual demands. For a substantial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
113
5
6

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(130 citation statements)
references
References 33 publications
6
113
5
6
Order By: Relevance
“…Rosenthal, Moore, and Flynn (1991) investigated the relationship between self-perceptions, including sexual self-esteem and sexual self-efficacy of 18-year-old males and females and their relationship to sexual risk taking. Results of their study showed that most of the respondents in this study felt relatively confident in their ability to engage in a wide range of sexual behaviors including purchasing condoms and discussing their use or delaying sexual intercourse until protection was available.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Rosenthal, Moore, and Flynn (1991) investigated the relationship between self-perceptions, including sexual self-esteem and sexual self-efficacy of 18-year-old males and females and their relationship to sexual risk taking. Results of their study showed that most of the respondents in this study felt relatively confident in their ability to engage in a wide range of sexual behaviors including purchasing condoms and discussing their use or delaying sexual intercourse until protection was available.…”
Section: Self-efficacymentioning
confidence: 99%
“…Another finding was that respondents recorded higher levels of confidence in discussing using condoms or contraceptives with a potential partner as means of pregnancy prevention as opposed to discussing condoms/ or contraception as means of safe sex. The authors explain the latter to be seen as embarrassing because it could be viewed as negatively reflecting on their partner's past sexual history (Rosenthal, Moore & Flynn, 1991).…”
Section: Self-efficacymentioning
confidence: 99%
“…The 8-item measure of sexual risk-taking behavior was based on the Youth Risk Behavior Surveillance (Brener, Collins, Kann, Warren, & Williams. 1995) and the Sexual Behavion^isk Scale (Rosenthal, Moore. & Flynn, 1991).…”
Section: Forced-choice Self-report Measuresmentioning
confidence: 99%
“…Sur\'eillance (Brener et al, 1995) and the Sexual Behavior/Risk Scale (Rosenthal et al, 1991). Only those adolescent women who had ever engaged in sexual intercourse with a male were instructed to respond to all five of the sexual/reproductive health-seeking behavior questions.…”
Section: Forced-choice Self-report Measuresmentioning
confidence: 99%
See 1 more Smart Citation